2017
DOI: 10.4267/2042/62674
|View full text |Cite
|
Sign up to set email alerts
|

Insights on processes of evolutionary tumor growth

Abstract: Application of traditional somatic evolutionary theory can offer an appropriate context for studying tumor growth at the molecular level. However, high degrees of heterogeneity (especially genome-level heterogeneity) within tumors coupled with a lack of common driver mutations have posed a challenge to the generally accepted stepwise concept of cancer evolution, where clonal expansion is the key. In order to account for multiple levels of heterogeneity and better understand tumor growth and progression, a new,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, while some studies have associated high CIN with poor patient outcomes and drug resistance [ 127 ], others have indicated that it is associated with better responses [ 4 , 128 ]. In fact, it has been indicated that targeting CIN for cancer therapy can induce genome chaos, which contributes to an increased CIN and therefore to the possible acquisition of proliferative advantages and resistance to therapy [ 129 , 130 ].…”
Section: The Role Of Cin In Anticancer Therapy Responsesmentioning
confidence: 99%
“…However, while some studies have associated high CIN with poor patient outcomes and drug resistance [ 127 ], others have indicated that it is associated with better responses [ 4 , 128 ]. In fact, it has been indicated that targeting CIN for cancer therapy can induce genome chaos, which contributes to an increased CIN and therefore to the possible acquisition of proliferative advantages and resistance to therapy [ 129 , 130 ].…”
Section: The Role Of Cin In Anticancer Therapy Responsesmentioning
confidence: 99%
“…In this regard, it has been indicated that chromosomal alterations in individual cancer cells (NCCAs) can lead to variable drug sensitivity, promoting the survival of a fraction of the tumor cell population [ 99 ] ( Figure 2 ). Further, according to Horne et al [ 100 ], the administration of high-dose chemotherapeutics can also result in the generation of new NCCAs, ultimately giving the disease a chance for recovery and resistance ( Figure 3 ). In fact, we demonstrated that low doses of Tamoxifen (TAM) promotes the production of specific chromosomal abnormalities in breast cancer cell lines, which could contribute to the selection of clones with proliferative advantages, thereby favoring cell survival and therapy resistance [ 101 ].…”
Section: Nccas Cin and Therapy Responsementioning
confidence: 99%
“…Now, the cancer genome sequencing project has proven otherwise, and interest in studying heterogeneity is strongly coming back. Interestingly, molecular cytogenetics approaches can play an important role in studying the mechanism of heterogeneity [ 37 - 40 ]. Third, there is an urgent need to rethink the genetic/genomic theories, as well as evolutionary theory, in the light of cellular evolution and disease initiation and progression.…”
Section: Introductionmentioning
confidence: 99%